Analysis on the Attitudes and Listening Habits of Music Students Toward Classical Music - He, Kunjin; Maneewattana, Chutima; Ren, Xiulei (Journal of Dhamma for Life, 2025)
This paper aims to explore the attitudes and listening habits of music students towards classical music. Through questionnaires and in-depth interviews with music students, this paper analyzes music students' knowledge of and interest in classical music as well as their listening habits and preferences. The research results show that there is diversity in attitudes towards classical music among music students, but more than half of the music students do not like classical music. Given that conservatory training is based on classical music, it seems that most music students may not like their major. In order to explore the reasons involved, the author summarized their listening habits through interviews. Meanwhile, the listening habits of music students are influenced by many factors, including personal cognition, personal interests and so on. This paper also offers suggestions on how to enhance music students' interest in and appreciation of classical music.